2013
DOI: 10.1007/s00380-013-0374-6
|View full text |Cite
|
Sign up to set email alerts
|

Diverse effects of prostaglandin E2 on vascular contractility

Abstract: Prostaglandin E₂ (PGE₂) is a major prostanoid produced under inflammatory situations. There have been controversial reports showing contractile or relaxant effect of PGE₂ on vascular tone in various types of blood vessels. Thus, it is still elusive whether and how PGE₂ modulates vascular tone. We here assessed the effects of PGE₂ on vascular contractility using different types of vasculatures isolated form rat. In endothelium-denuded aortas and mesenteric arteries, PGE₂ (1 nM-10 μM) concentration-dependently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…EP 3 receptor stimulation enhanced the endothelial barrier and suppressed vascular permeability without affecting the contraction of mural cells or local blood flow. We previously reported that an EP 3 receptor agonist induced contraction in large or splanchnic arteries, while it did not influence contraction in small arteries, for example the tail artery (Kobayashi et al ., ; Kida et al ., ). Smooth muscle cells in small vessels are unlikely to be responsive to EP 3 receptor‐mediated signalling.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…EP 3 receptor stimulation enhanced the endothelial barrier and suppressed vascular permeability without affecting the contraction of mural cells or local blood flow. We previously reported that an EP 3 receptor agonist induced contraction in large or splanchnic arteries, while it did not influence contraction in small arteries, for example the tail artery (Kobayashi et al ., ; Kida et al ., ). Smooth muscle cells in small vessels are unlikely to be responsive to EP 3 receptor‐mediated signalling.…”
Section: Discussionmentioning
confidence: 97%
“…Data are presented as means ± SEM. ◀ reported that an EP3 receptor agonist induced contraction in large or splanchnic arteries, while it did not influence contraction in small arteries, for example the tail artery (Kobayashi et al, 2011;Kida et al, 2014). Smooth muscle cells in small vessels are unlikely to be responsive to EP3 receptor-mediated signalling.…”
Section: Figurementioning
confidence: 99%
“…This suggests that EP3’s vasoconstrictor activity can blunt effects of vasodilator EPs (EP2 and/or 4) to take a part in PGE 2 ‐mediated control of renal blood flow or systemic blood pressure. Indeed, PGE 2 is found to evoke contractions of some isolated vessels that are inhibited by antagonizing EP3 . However, vasoconstrictor responses of isolated vessels to PGE 2 are also found to be abolished by TP antagonism .…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, PGE 2 is found to evoke contractions of some isolated vessels that are inhibited by antagonizing EP3. [14][15][16] However, vasoconstrictor responses of isolated vessels to PGE 2 are also found to be abolished by TP antagonism. 17,18 Moreover, we have recently shown that TP −/− removes most of the contraction evoked by PGE 2 in mouse abdominal aorta.…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 and PGD 2 are important modulators of vasodilation, and PGE 2 can potentiate an increase in vascular permeability, promoted by mediators of this phenomenon, with a consequent formation of edema [188,189]. Studies using pharmacological treatment with non-steroidal anti-inflammatory compounds were crucial in demonstrating the participation of these COXs-derived lipid mediators on edema [126,190] and hyperalgesia [135], induced by B. asper sPLA 2 s. In addition, studies demonstrating that MT-III and MT-II upregulated COX-2 protein expression in peritoneal leukocytes without altering the constitutive expression of COX-1 evidenced the ability of these venom PLA 2 s to influence downstream cyclooxygenase isozymes and suggested this as a mechanism by which these sPLA 2 s induced the production of prostaglandins [162,163].…”
Section: Influence Of Bothrops Svpla 2 S On Pathways Of Arachidonic Acid Metabolismmentioning
confidence: 99%